2014
DOI: 10.1002/mop.28780
|View full text |Cite
|
Sign up to set email alerts
|

A compact modified triangular CPW‐fed antenna with multioctave bandwidth

Abstract: This article presents the results of a compact modified triangular CPW‐fed antenna that exhibits multioctave performance. This modification significantly improves the antenna's impedance bandwidth by 198% over an ultra‐wideband (UWB) frequency range from 3.06 to 35 GHz. The return‐loss (S11) performance over this frequency range is designed to be better than −10 dB. These characteristics make the proposed antenna an excellent candidate for numerous UWB applications and next generation communication systems. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The narrow bandwidth [12] is used for wireless application. The slits loaded in the ground plane offers better impedance matching [2]. The ELC provides negative permeability characteristics due to its stop band behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The narrow bandwidth [12] is used for wireless application. The slits loaded in the ground plane offers better impedance matching [2]. The ELC provides negative permeability characteristics due to its stop band behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development of ultra‐wideband (UWB) antennas enabling high data transmission rates and low power consumption, and simple hardware configuration in communication application has received attention . The Federal communication commission (FCC) allocated the frequency band 3.1–10.6 GHz for commercial UWB systems in 2002 .…”
Section: Introductionmentioning
confidence: 99%
“…The Federal communication commission (FCC) allocated the frequency band 3.1–10.6 GHz for commercial UWB systems in 2002 . Despite the approval of the FCC for the UWB to operate 3.1–10.6 GHz, it may be necessary to avoid potential interferences with other existing communication systems, such as Worldwide Interoperability for the Microwave Access (WiMAX) operating at 3.3–3.6 GHz; Wireless Local Area Network (WLAN) is operated at 5.15–5.825 GHz . Therefore, UWB antenna with notched characteristics at these frequency bands is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wireless local area network (WLAN) and worldwide interoperability for microwave access (WiMAX) have been widely applied in mobile devices, such as handheld computers and intelligent phones [2]. Also many efforts in UWB antenna fields have been reported that more descriptions come in [3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%